Patterns of prescription, over-the-counter, and herbal medication use among pregnant women in Buraydah, Saudi Arabia: a cross-sectional study - Almutairi, Masaad S.; Saeed, Mustafa S.; Alowias, Hessa; Alharbi, Afnan; Alnezary, Faris S.; Almohammed, Omar A. (Frontiers in Pharmacology, 2026)
BackgroundMedication use during pregnancy is a significant public health consideration due to potential risks that certain medication can cause to both the mother and the developing fetus. Understanding regional patterns of medication use is crucial for targeted patient counseling and pharmacovigilance. This study aimed to characterize the prevalence, types, and predictors of prescription, over-the-counter (OTC), and herbal medication use among pregnant women in Buraydah, Saudi Arabia.MethodsA cross-sectional survey was conducted among 407 pregnant women receiving antenatal care at the Maternity and Children Hospital in Buraydah. Data on demographics, clinical characteristics, and medication use were collected using a structured questionnaire and analyzed using descriptive statistics and multivariable logistic regression.ResultsMedication use was found to be highly prevalent. Almost all participants (98.3%) used pregnancy-related supplements, with folic acid being the most common. Prescription medication for short-term conditions was reported by 43.5% of women, with antibiotics (62.1%) and analgesics (42.9%) being the most frequent. In addition 19.4% of them used medications for chronic conditions, primarily hormone replacement therapy (44.3%) for hypothyroidism. OTC analgesics were used by half (50%) of the 36.9% of women taking nonprescription drugs; 19.4% of them used herbal medicine, with ginger being the most common (44.7%) ingredient for nausea. Further, women in their second (OR: 6.75) and third (OR: 8.71) trimesters were more likely to use short-term prescription medications compared to those in their first trimester.ConclusionMedication and supplement use was found to be widespread among the studied cohort of pregnant women. The findings emphasize the need for enhanced pharmacovigilance and proactive patient counseling by healthcare providers, particularly pharmacists, to ensure maternal and fetal safety.